FEATURES OF REGULATION THE LEGAL RELATIONSHIP BETWEEN CLIENT AND LAWYER IN LEGAL FIRMS - Maxmudov Umid Baxronovich (Galaxy International Interdisciplinary Research Journal, 2022)
The paper analyzes and compares such concepts as “legal service” and “legal assistance”. Lawyers devote the article to the study of the peculiarities of the legal regulation of the conclusion and execution of contracts for the provision of services. The conclusion is made that legal services are one of the complex and undeveloped in the theory of types of services that require recommendations to address gaps in the current legislation. An analysis is made of the practical application of contracts for the provision of legal services and contracts of commission concluded by lawyers. Concrete proposals are identified for amendments to the Law “On the Advocacy and the Bar of the Republicussian Federation”, which, in our opinion, will help strengthen the independence of the institution of the bar in the Russian Federation and eliminate differences on the qualification of the legal aid agreement.